Potential Pharmaceutical Applications of Quercetin in Cardiovascular Diseases - Paraskevi Papakyriakopoulou; Nikolaos Velidakis; Elina Khattab; Georgia Valsami; Ioannis Korakianitis; Nikolaos PE Kadoglou (MDPI AG, 2022)
Quercetin, as a member of flavonoids, has emerged as a potential therapeutic agent in cardiovascular diseases (CVDs) in recent decades. In this comprehensive literature review, our goal was a critical appraisal of the pathophysiological mechanisms of quercetin in relation to the classical cardiovascular risk factors (e.g., hyperlipidemia), atherosclerosis, etc. We also assessed experimental and clinical data about its potential application in CVDs. Experimental studies including both in vitro methods and in vivo animal models mainly outline the following effects of quercetin: (1) antihypertensive, (2) hypolipidemic, (3) hypoglycemic, (4) anti-atherosclerotic, and (5) cardioprotective (suppressed cardiotoxicity). From the clinical point of view, there are human studies and meta-analyses implicating its beneficial effects on glycemic and lipid parameters. In contrast, other human studies failed to demonstrate consistent favorable effects of quercetin on other cardiometabolic risk factors such as MS, obesity, and hypertension, underlying the need for further investigation. Analyzing the reason of this inconsistency, we identified significant drawbacks in the clinical trials' design, while the absence of pharmacokinetic/pharmacodynamic tests prior to the studies attenuated the power of clinical results. Therefore, additional well-designed preclinical and clinical studies are required to examine the therapeutic mechanisms and clinical efficacy of quercetin in CVDs.